ASSOCIATION BETWEEN LIPID PROFILE OF CIRRHOTIC PATIENTS AND PROGNOSTIC SCORES - RAZA , A; KHAN , MSN; KHAN , AR; NAEEM , M; SERWER , S; ASLAM , MA (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Hepatology & Medicine Department of the hospital from January 2022 to January 2023 to assess the association of the lipid profile of cirrhotic patients with scores including MELD and Child-Pugh. The study included patients aged > 18 years who had cirrhosis due to hepatitis C infection. Demographic data, biochemical parameters, and MELD and Child-Pugh scores of the participants were recorded. Data were analyzed using SPSS version 23.0. Results showed a statistically significant inverse correlation between lipid fractions and Child-Pugh score (P<0.001). The higher MELD score was correlated with lower TG (P=0.003), VLDL (P=0.030), LDL (P<0.001), HDL (P<0.001), and TC (P<0.001) levels. There is a significant association between MELD and Child-Pugh prognostic markers and reduced lipid profiles of cirrhotic patients. These results suggest using a lipid profile as a supplemental tool for evaluating liver disease.